2010
DOI: 10.1007/s12594-010-0076-y
|View full text |Cite
|
Sign up to set email alerts
|

Age of the Vastan lignite in context of some oldest cenozoic fossil mammals from India

Abstract: A highly diverse assemblage of mammal and other continental vertebrate fossils is reported in recent years from Vastan lignite mine (21 o 25'47" N; 73 o 07'30" E). Its importance in testing palaeobiogeographic hypothesis of mammalian dispersal in to or out of India has necessitated a definite age of the sequence. Nummulites burdigalensis is the only age diagnostic foraminifer in the section. This species is widespread in the Indian sedimentary basins and used to mark Early Eocene strata. In the present study t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(22 citation statements)
references
References 5 publications
1
21
0
Order By: Relevance
“…Further the presence of Homotryblium tenuispinosum, Homotryblium pallidum and Polysphaeridium subtile dinocysts in the assemblage also confirms Ypresian to be the lower age limit of the Surkha lignite. The age inferred for the present study is in agreement with the other studies of Cambay Shales (Garg et al, 2008;Punekar and Saraswati, 2010;Rao et al, 2013).…”
Section: Age Of Surkha Lignitesupporting
confidence: 93%
“…Further the presence of Homotryblium tenuispinosum, Homotryblium pallidum and Polysphaeridium subtile dinocysts in the assemblage also confirms Ypresian to be the lower age limit of the Surkha lignite. The age inferred for the present study is in agreement with the other studies of Cambay Shales (Garg et al, 2008;Punekar and Saraswati, 2010;Rao et al, 2013).…”
Section: Age Of Surkha Lignitesupporting
confidence: 93%
“…The vertebrate-bearing horizon occurs between the two main lignite seams in the mine, about 1 m above the older seam (Lignite 2). The age of the vertebrate-bearing bed was previously considered early Cuisian (~53 Ma) based on the occurrence of an index nummulitid foraminiferan, Nummulites burdigalensis burdigalensis, about 15 m above this layer (Rana et al, 2004;Sahni et al, 2006;Punekar and Saraswati, 2010). Garg et al (2008) suggested a slightly older age, betweeñ 54 and 55 Ma, on the basis of dinoflagellate cysts from near the fossil mammal horizon of the same section.…”
Section: Introductionmentioning
confidence: 99%
“…The foraminifera are found in the shale part of the sequence. The upper part of the mine section is assigned to SBZ 10 on the basis of the occurrence of Nummulites burdigalensis burdigalensis (Punekar & Saraswati, 2010). Garg et al (2008) assigned the section to the upper SBZ 7 to lower SBZ 10 based on dinoflagellates.…”
Section: Geology and Stratigraphymentioning
confidence: 99%
“…However, much less work has been done to describe the responses of the larger and smaller benthic or planktic foraminifera from these early Eocene sections of western India. The well-preserved foraminifera in the sections (Samanta, 1970;Saraswati et al, 2012, Punekar & Saraswati, 2010 provided the opportunity to investigate the paleo-environmental conditions and response of foraminiferal assemblages to the hyperthermal events in tropical India.…”
Section: Introductionmentioning
confidence: 99%